Total internet blackout (Myanmar) - Voidly (Voidly Global Censorship Index, 2021)
CRITICAL severity censorship detected in Myanmar. Data sourced from OONI.
Censorship Incident ID: MM-2021-0002. Severity: critical. Confidence: 90%